The Australian Burden of Disease Study: impact and causes of illness and death in Aboriginal and Torres Strait Islander people, 2011 - Fadwa Al-Yaman (Sax Institute, 2017)
This study estimates fatal and nonfatal disease burden among Indigenous Australians in 2011 and compares it with non-Indigenous Australians. The study found that there were 284 years lost per 1000 people because of premature death or living with ill health. Most of the disease burden was from chronic diseases (64%), particularly mental and substance-use disorders, injuries, cardiovascular diseases, cancer and respiratory diseases. The burden of disease was higher among males (54%) than females (46%) and higher for fatal (53%) than for nonfatal burden (47%). The disease groups with the highest burden varied by age group, with mental and substance-use disorders and injuries being the largest disease groups among those aged 5-44 years, and cardiovascular disease and cancer becoming more prominent among those aged 45 and older. Large disparities existed between Indigenous and non-Indigenous Australians, with the total burden being 2.3 times the non-Indigenous rates, fatal burden being 2.7 times and nonfatal burden being 2 times.